Fluoridation of water supplies and cancer mortality. III: A re-examination of mortality in cities in the USA. - Kinlen, L; Doll, R (1981)
The mortality from cancer in the 10 largest cities in the USA that have had fluoridated water supplies since before 1957 was somewhat higher in 1970 than in the large non-fluoridated cities that we have examined. The relative excess has not increased since 1950, if allowance is made for changes in the sex, age, and ethnic group constitution of the population by any of the standard methods. On the contrary, it has decreased slightly no matter which of the appropriate methods of comparison is chosen. We thank Angela Hewitt for help with the analyses and the National Center for Health Statistics, Maryland, for making available mortality data relating to the cities covered by this study.